THE METHOD OF SUMMARY MODELING POLLUTION OF ATMOSPHERE FOR MANAGEMENT AND BUILDING CONSTRUCTION’S DECISION - Valeriy Nikolaevich Azarov; Sergey Arcadievich Koshkarev; Andrey Yurievich Nedre; Yury Andreivich Nedre; Roman Mikhailovich Sarkisov; Pavel Alekseevich Sidyakin (Современная наука и инновации)
The article is devoted to the problem of improving of summary calculation system of air pollution and possible simplifications and view of the results in an interactive form. The article presents the results of summary calculations of emissions of polluting substances into the atmosphere from enterprises within urban areas in the number of small towns of the Russian Federation. The estimation of the values of the criterion, allowing simplification, and considered possibilities of the use of some other indicators (criteria) is performed. The methods of implementation of the urban planning decisions based on the results of summary calculations in industrial areas and cities of the Russian Federation are considered.